Feathers #1. - Corona, Jorge (Feathers., 2015)
WHY WE LOVE IT: In the footsteps of Archaia titles Rust, Iron, Will o' the Wisp, and The Reason for Dragons, debut writer-artist Jorge Corona brings a brand-new voice to the comics industry with Feathers. With our passion for working with fresh talent, we could not be happier to introduce his work to a wider audience. WHY YOU'LL LOVE IT: There's never been a better time for fantastic, all-ages comics that embrace both the darkness and beauty in life. Fans of Avatar: Legend of Korra, Mike Mignola, and Amulet will fall in love with Poe, the boy covered in feathers. WHAT IT'S ABOUT: A recluse boy born covered in feathers must help his first-ever friend, a young girl named Bianca, as she tries to return to her home beyond the slums of the Maze. They must dodge street gangs and child-snatchers along the way, and perhaps together will learn the secrets to his mysterious past.